Excessive ammonium assimilation by plastidic glutamine synthetase causes ammonium toxicity in Arabidopsis thaliana - Takushi Hachiya (Nature Portfolio, 2021)
Ammonium is an important nitrogen source for plants but excess ammonium impairs growth. Here the authors show that ammonium toxicity results from assimilation by GLUTAMINE SYNTHETASE 2 in the plastids which results in excess proton accumulation and acidity stress.